Analysis of Land Value Changes and Its Correlation with the Existence of Tourism and Accessibility in 2017-2024 - Putri, Ananda Sandriana; Amarrohman, Fauzi Janu; Yusuf, Muhammad Adnan (BHUMI: Jurnal Agraria dan Pertanahan, 2024)
Abstract: The rapid growth in tourism has had a direct impact on the local economy and the potential for changes in land value. This study aims to analyze the influence of tourist attractions and accessibility on land value changes in Getasan District from 2017 to 2024, amidst the significant growth of tourism. The research employed a descriptive and quantitative approach to analyze the data comprehensively. Quantitative analysis was carried out using multiple linear regression to evaluate the influence of proximity to tourist attractions and road accessibility on land value. The land value zone maps for 2017 and 2021 were obtained from the Semarang Regency Land Office, while the 2024 land value zone was created through the update of the 2021 zone. This update resulted in 130 zones with 688 sample points collected through field surveys based on fair market prices. Multiple linear regression analysis was conducted to evaluate the influence of straight-line distance from the zone centroid to tourist attractions and collector roads. The results showed that the p-value in the simultaneous test was 0.03647 (? 0.05), indicating that tourist attractions and accessibility have a simultaneous and significant influence on land value zone changes, with an impact size of 7.87%. These findings highlight the urgency of considering the rapidly developing tourism sector and accessibility in regional management and development, given their effect on land values in Getasan. Keywords: Getasan District, Kopeng Tourism, Land Value Zone